DETERMINATION OF ACC SECTORS CAPACITY BY THE EUROCONTROL METHODOLOGY - Луппо, О.Є.; Глушко, О.В.; Долматова, Д.М. (Proceedings of National Aviation University, 2012)
The article deals with the main characteristics and perspectives of Eurocontrol methods for the determination of ACC capacity, was considered the ATC Capacity Analyzer tool (CAPAN), and fast ACC capacity evaluation tool (FACET), was studied the reorganized ATC mathematical simulator (RAMS).